TCM perspective and treatment of woman’s depression and anxiety symptoms related to infertility - Teo, Yen Ting (2016)
Traditional Chinese Medicine (TCM) believes that the mind, spirit and body are inseparably connected. Unstable emotions like depression and anxiety may result in systemic dysfunction, internal injury and a series of consequences. TCM therapy focuses in achieving homeostasis among the seven emotions. This study aimed to evaluate the prevalence of depression and anxiety in infertile women, hence to understand TCM infertility treatment via investigating the etiology related to TCM principles. Four patterns of infertility in TCM’s context were introduced to highlight the impact of psychological stress on liver Qi stagnation. Questionnaires were designed specifically to target a total of 60 infertile patients from Singapore Tong Chai Medical Institution and NTU TCM clinic. Zung Self-Rating Depression Scale (ZSDS) and Self-Rating Anxiety Scale (SAS) were completed and the respective scores (p<0.0001) were statistically analyzed in comparison to the control data. Results shown that among the 36% of women has depression, 4% were in severe condition; 28% had anxiety and out of 3% were in severe anxiety disorder. The relatedness of depression and anxiety in infertility was further concluded. Psychosocial intervention was suggested in order to raise awareness on the effect of depression and anxiety in infertility, which may also then complicate the treatment process.